Reductive Deoximation of Certain Oximes by Electrolytically Generated Vanadium(II) in Aqueous Sulphuric Acid Media - Vasantkumar Pai, K.; Vasudeva Nayak, P.; Sheregara, B.S. (Asian Journal of Chemistry, 2010)
Vanadium(II) species generated by the cathodic reduction of vanadium(II) sulphate using mercury pool cathode under nitrogen atmosphere has been characterised by UV-visible spectra and by the determination of redox potential of V(III)/v(II) couple. The purity of V(II) species has been tested by potentiometric titration with standard cerium(IV) solution where the species gets oxidised to V(V) in three steps corresponding to three equivalent points. The reductive estimation of hydroxylamine hyrochloride and its keto and aldehyde oxime derivatives using V(II) was carried out. The reaction products were isolated, indentified and characterised by the literature methods. The utility of V(II) as a reductant in analytical studies has been highlighted.